Genetic profile of adult T‐cell leukemia/lymphoma in Okinawa: Association with prognosis, ethnicity, and HTLV‐1 strains. Issue 3 (31st January 2021) - Sakihama, Shugo; Morichika, Kazuho; Saito, Rumiko; Miyara, Megumi; Miyagi, Takashi; Hayashi, Masaki; Uchihara, Junnosuke; Tomoyose, Takeaki; Ohshiro, Kazuiku; Nakayama, Shingo; Nakachi, Sawako; Morishima, Satoko; et al.
Abstract: Genetic alterations in adult T‐cell leukemia/lymphoma (ATLL), a T‐cell malignancy associated with HTLV‐1, and their clinical impacts, especially from the perspective of viral strains, are not fully elucidated. We employed targeted next‐generation sequencing and single nucleotide polymorphism array for 89 patients with ATLL in Okinawa, the southernmost islands in Japan, where the frequency of HTLV‐1 tax subgroup‐A (HTLV‐1‐ tax A) is notably higher than that in mainland Japan, where most ATLL cases have HTLV‐1‐ tax B, and compared the results with previously reported genomic landscapes of ATLL in mainland Japan and the USA. Okinawan patients exhibited similar mutation profiles to mainland Japanese patients, with frequent alterations in TCR/NF‐ĸB (eg, PRKCB, PLCG1, and CARD11 ) and T‐cell trafficking pathways ( CCR4 and CCR7 ), in contrast with North American patients who exhibited a predominance of epigenome‐associated gene mutations. Some mutations, especially GATA3 and RHOA, were detected more frequently in Okinawan patients than in mainland Japanese patients. Compared to HTLV‐1‐ tax B, HTLV‐1‐ tax A was significantly dominant in Okinawan patients with these mutations ( GATA3, 34.1% vs 14.6%, P  = .044; RHOA, 24.4% vs 6.3%, P  = .032), suggesting the contribution of viral strains to these mutation frequencies. From a clinical viewpoint, we identified a significant negative impact of biallelic inactivation of PRDM1 ( P  = .027) in addition to the previously reported PRKCB mutations, indicating the importance of integrated genetic analysis. This study suggests that heterogeneous genetic abnormalities in ATLL depend on the viral strain as well as on the ethnic background. This warrants the need to develop therapeutic interventions considering regional characteristics. Abstract : Targeted next‐generation sequencing and single nucleotide polymorphism array were applied to analyze aggressive adult T‐cell leukemia/lymphoma in Okinawa, which were not included in prior genomic studies. Our results showed that HTLV‐1 tax subgroup‐A was associated with high alteration frequencies in GATA3 and RHOA . Clinically, biallelic alterations, not heterozygous deletions or mutations, of PRDM1 were significantly associated with poor prognosis.